Recurrent gastrointestinal bleeding in a 16-year-old with enteric perforation peritonitis: a surgical challenge - Jain, Ankit; Verma, Neha; Malhotra, A. K.; Mittal, Vinamra (International Journal of Research in Medical Sciences, 2025)
We present a rare and complex case of recurrent lower gastrointestinal bleeding following emergency laparotomy for enteric perforation peritonitis in a 16-year-old boy. Despite initial surgical management with primary repair, the patient developed persistent rectal bleeding, leading to hemodynamic instability and necessitating extensive investigations. Upper gastrointestinal endoscopy and computed tomography (CT) angiography failed to localize the bleeding source. A second laparotomy revealed diffuse mucosal oozing in the terminal ileum, prompting a right hemicolectomy with ileo-ascending side-to-side anastomosis and diversion loop ileostomy. Histopathology confirmed typhoid enteritis. This case underscores the importance of early recognition, aggressive management, and consideration of diffuse mucosal pathology in postoperative gastrointestinal bleeding, especially when standard diagnostics are inconclusive. Multidisciplinary collaboration and timely surgical intervention were crucial in achieving a favorable outcome. The case highlights the need for individualized surgical strategies to manage refractory bleeding in pediatric patients with enteric perforation.